2020
DOI: 10.1021/jacs.0c10471
|View full text |Cite
|
Sign up to set email alerts
|

Direct Enantioselective C(sp3)–H Acylation for the Synthesis of α-Amino Ketones

Abstract: A direct enantioselective acylation of α-amino C(sp 3 )−H bonds with carboxylic acids has been achieved via the merger of transition metal and photoredox catalysis. This straightforward protocol enables cross-coupling of a wide range of carboxylic acids, one class of feedstock chemicals, with readily available N-alkyl benzamides to produce highly valuable α-amino ketones in high enantioselectivities under mild conditions. The synthetic utility of this method is further demonstrated by gram scale synthesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(77 citation statements)
references
References 87 publications
1
67
0
1
Order By: Relevance
“…It has been reported that single-electron oxidation of bromide anion by photoexcited photocatalyst can generate bromine radical ( E 1/2 [Ir(III*/II)] = +1.21 V vs SCE in CH 3 CN; E 1/2 ox [Br − /Br·] = +0.80 V vs SCE in DME) 51 54 . According to the literature precedent and our previous mechanistic experiments 38 , 51 54 , we hypothesize that the catalytic reaction is initiated by oxidative addition of Ni(0) catalyst I to an in situ-activated carboxylic acid to afford Ni(II) species II . Subsequent trapping of prochiral benzylic radicals generated from the bromine-radical-mediated HAT process provides Ni(III) complex III , which undergoes reductive elimination to yield the desired product and Ni(I) species IV .…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…It has been reported that single-electron oxidation of bromide anion by photoexcited photocatalyst can generate bromine radical ( E 1/2 [Ir(III*/II)] = +1.21 V vs SCE in CH 3 CN; E 1/2 ox [Br − /Br·] = +0.80 V vs SCE in DME) 51 54 . According to the literature precedent and our previous mechanistic experiments 38 , 51 54 , we hypothesize that the catalytic reaction is initiated by oxidative addition of Ni(0) catalyst I to an in situ-activated carboxylic acid to afford Ni(II) species II . Subsequent trapping of prochiral benzylic radicals generated from the bromine-radical-mediated HAT process provides Ni(III) complex III , which undergoes reductive elimination to yield the desired product and Ni(I) species IV .…”
Section: Resultsmentioning
confidence: 88%
“…Our investigation began with an exploration of reaction conditions for the coupling of 4-ethylbiphenyl and 3-phenylpropanoic acid (Table 1 ). Based on previously reported elegant strategies and our recent conditions for carboxylic acid activation in ketone synthesis 38 , 56 60 , dimethyl dicarbonate (DMDC) was chosen as the activating agent to generate mixed anhydride in situ from carboxylic acids. After an extensive study of reaction parameters (also see Supplementary Table 1 ), we were delighted to find that a simple chiral nickel/bis(oxazoline) catalyst and a known Ir-photocatalyst could provide the acylation product in 85% yield and 94% ee (entry 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2020, Huo and co-workers reported a direct enantioselective acylation of -amino C(sp 3 )-H bonds for the synthesis of -amino ketones (Scheme 9). 25 The reaction was catalyzed by an iridium-based photocatalyst and a nickel cocatalyst containing a chiral bisoxazoline ligand L10 in the presence of dimethyl dicarbonate (DMDC) as the activator, and converted a carboxylic acid into a mixed anhydride in situ. Mechanistic investigations suggested that the C(sp 3 )-H bond of 33 is cleavage by photocatalytically generated bromine radicals to produce an -aminoalkyl radical, which is involved in the further stereoselective transformation governed by the chiral nickel catalyst.…”
Section: Short Review Synthesismentioning
confidence: 99%